Audit reports of financially distressed companies: emphasis of matter (EOM) versus disclaimers - Ismail, Hashanah; Mustapha, Mazlina (David Publishing, 2013)
This paper examines audit reports issued to 39 Malaysian listed companies in financial distress categorized as Practice Note 17 (PN17) companies by Bursa Malaysia. The study finds that for companies which experienced financial distress, the audit reports are not similar, despite all companies are similarly troubled financially. Companies receive either a disclaimer or an emphasis of matter (EOM) report. The study finds that which of the two reports is given is associated with three variables: current-year operating loss, shareholders’ deficit, and default status, implying that audit reports do convey information that financial distress is not of the same level and severity among PN17 companies.